GESTIÓN ADMINISTRATIVA Y SU INFLUENCIA EN LA MOTIVACIÓN EN LA VENTA POR CATÁLOGO DE LA EMPRESA JDR&S. - Ruiz Salvatierra, Edilma del rocio (2019)
The first form of exchange of goods, occurs with barter, the root of what That would be direct sales later. The first direct selling sellers appeared in the Middle Ages in Europe, in England; they were street vendors, known as the "Chapmen", who traveled regularly from Scotland to the north of England, with products that they bought and then resold from town to town, from house to house. (AEVD Ecuadorian Association of Direct Selling, 2016)